Analisis Kebutuhan Buku Cerita Bergambar sebagai Pengantar Bermain di Taman Kanak-Kanak - Astuti, Budi; Sumarno, Sumarno; Dwijayanti, Ida (Medan Resource Center, 2024)
The availability of picture storybooks is a crucial component of early childhood education. This research aims to describe and analyze the needs for storybooks among Kindergarten students through a questionnaire. At an early age, play is an essential activity that supports children's cognitive, social, emotional, and motor development. The storybooks used in this process must have specific characteristics that captivate children's interest while aligning with educational objectives. The research methods employed include observations, interviews with kindergarten teachers, and content analysis of popular storybooks among young children. The findings are intended to serve as a foundation for developing educational materials, particularly picture storybooks that facilitate play-based learning for kindergarten students. The ultimate goal is to enhance the quality of educational resources available to young learners, ensuring they are both engaging and educationally beneficial.